Анализ рынка пластиковых карт в Украине - Майданевич, Ю.П.; Павлюкевич, А.С. (Культура народов Причерноморья, 2014)
В статье проведен анализ рынка пластиковых карт в Украине. Определен рейтинг банков по выпуску и использованию платежных карт украинцами. Рассмотрена динамика использования платежных карт по Украине. Обоснована необходимость дальнейшего распространения пластиковых карт среди украинцев. У статті проведений аналіз ринку пластикових карт в Україні. Визначено рейтинг банків з випуску та використанню платіжних карт українцями. Розглянута динаміка використання платіжних карт по Україні. Обґрунтовано необхідність подальшого поширення пластикових карт серед українців. In the article a market of plastic cards analysis is conducted in Ukraine. In 2012 jars are produce about 62,7 million payment cards. The amount of payment cards exceeds the quantity of population of country considerably. It means that one or nearly every citizen has a few plastic cards. The permanent leader of market of bank maps in Ukraine is remained by «Privatbank». Him the 35,8 million produced payment cards belong to, that is 51,32 %. At the same time at a bank high index of nonactive maps - Credit card that people do not use, or use extremely rarely. On 01.01.2013 nonactive bank maps Privatbank are 55 % from all produced by a bank. This index increases thus. On beginning 2012 year nonactive maps of Privatbank were 46 %. Stake of active maps in a lump sum produced by a bank higher than all in JK Ukrsibbank, ABAS Ukrgazbank and JK Raifaizen Bank Aval. The maps of these issuers are actively used by their holders. Rating of banks is certain on producing and use of payment cards Ukrainians. By leaders on volume active payment cards there are JK of КБ Privatbank (almost half from a general volume), propulsion MODULE «Savings bank » and propulsion MODULE of «Raifaizen Bank Aval»(for 9 %). The same jars have the ramified network Similarly in the article the dynamics of the use of payment cards is considered on Ukraine. Leaders it is been Kyiv, Dnepropetrovsk and Donetsk to the area. The necessity of further distribution of plastic cards is reasonable among Ukrainians, as one of instruments of reduction of available appeal in a country.